Patterns of microbial diversity along a salinity gradient in the Guerrero Negro solar saltern, Baja CA Sur, Mexico - Dillon, Jesse G.; Carlin, Mark; Gutierrez, Abraham; Nguyen, Vivian; McLain, Nathan (Frontiers in Microbiology, 2013)
The goal of this study was to use environmental sequencing of 16S rRNA and bop genes to compare the diversity of planktonic bacteria and archaea across ponds with increasing salinity in the Exportadora de Sal (ESSA) evaporative saltern in Guerrero Negro, Baja CA S., Mexico. We hypothesized that diverse communities of heterotrophic bacteria and archaea would be found in the ESSA ponds, but that bacterial diversity would decrease relative to archaea at the highest salinities. Archaeal 16S rRNA diversity was higher in Ponds 11 and 12 (370 & 380 g l-1 total salts respectively) compared to Pond 9 (180 g l-1 total salts). Both Pond 11 and 12 communities had high representation (47 and 45% of clones respectively) by Haloquadratum walsbyi-like (99% similarity) lineages. The archaeal community in Pond 9 was dominated (79%) by a single uncultured phylotype with 99% similarity to sequences recovered from the Sfax saltern in Tunisia. This pattern was mirrored in bop gene diversity with greater numbers of highly supported phylotypes including many Haloquadratum-like sequences from the two highest salinity ponds. In Pond 9, most bop sequences, were not closely related to sequences in databases. Bacterial 16S rRNA diversity was higher than archaeal in both Pond 9 and Pond 12 samples, but not Pond 11, where a non-Salinibacter lineage within the Bacteroidetes >98% similar to environmental clones recovered from Lake Tuz in Turkey and a saltern in Chula Vista, CA was most abundant (69% of community). This OTU was also the most abundant in Pond 12, but only represented 14% of clones in the more diverse pond. The most abundant OTU in Pond 9 (33% of community) was 99% similar to an uncultured gammaproteobacterial clone from the Salton Sea. Results suggest that the communities of saltern bacteria and archaea vary even in ponds with similar salinity and further investigation into the ecology of diverse, uncultured halophile communities is warranted.